2022
DOI: 10.1007/s11042-022-14006-4
|View full text |Cite
|
Sign up to set email alerts
|

Redefining food safety traceability system through blockchain: findings, challenges and open issues

Abstract: In the last few decades, there has been an increase in food safety and traceability issues. To prevent accidents and misconduct, it became essential to establish Food Safety Traceability System (FSTS) to trace the food from producer to consumer. The traceability systems can help track food in supply chains from farms to retail. Numerous technologies such as Radio Frequency Identification (RFID), sensor networks, and data mining have been integrated into traditional food supply chain systems to remove unsafe fo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 38 publications
(11 citation statements)
references
References 129 publications
0
6
0
Order By: Relevance
“…It does not require central entity for oversight. Moreover, “smart contracts” developed within the blockchain can specify the requirements for food safety that the products need to be checked against (Singh et al., 2022). A great variety of options is available for the data and documents that can be included depending on the design and acceptable volume of data, which does not have to be exhaustive for providing relevant information.…”
Section: Modern Systems Fed By Numerous Real‐time and Diverse Datamentioning
confidence: 99%
“…It does not require central entity for oversight. Moreover, “smart contracts” developed within the blockchain can specify the requirements for food safety that the products need to be checked against (Singh et al., 2022). A great variety of options is available for the data and documents that can be included depending on the design and acceptable volume of data, which does not have to be exhaustive for providing relevant information.…”
Section: Modern Systems Fed By Numerous Real‐time and Diverse Datamentioning
confidence: 99%
“…For example, Lopez-Galvez et al [ 12 ] examined potential tensions between microbiological safety and environmental sustainability in the supply chain of fresh produce, addressing issues throughout the food supply chain, from primary production to end-of-life, including handling, processing industry, retailers, and consumers. On the other hand, other studies have explored the design and implementation of food safety standards, traceability systems, and quality control mechanisms [ [21] , [22] , [23] ]. These studies have identified key factors and challenges impacting food safety in various supply chain contexts, such as information asymmetry [ 24 ], moral hazard [ 13 ], producer behavior [ 25 ], consumer behavior, and environmental impacts [ 12 ].…”
Section: Literature Reviewmentioning
confidence: 99%
“…The architecture is designed with both available resources and the specific characteristics of a group of people with a different perspective 25–28 . Most of the consumer utilizes IoT application with intellectual ability to form their life more comfortable, and they typically intercommunicate with IoT devices via experiential interfaces offered by the edge or cloud instead of interacting with IoT devices.…”
Section: Edge Computing Architecturementioning
confidence: 99%
“…The architecture is designed with both available resources and the specific characteristics of a group of people with a different perspective. [25][26][27][28] Most of the consumer utilizes IoT application with intellectual ability to form their life more comfortable, and they typically…”
Section: Edge-centric Iot Architecturementioning
confidence: 99%